When Science Meets Nature: What Research Reveals about the Transformative Power and Meaningfulness of Contextual Teaching in Environmental Science Learning - Lintang Auliya Kurdiati (Universitas Tidar, 2026)
Environmental sustainability and scientific literacy are increasingly critical in contemporary education, yet science instruction often remains abstract and disconnected from real-world contexts. This systematic review aims to analyze the implementation characteristics of Contextual Teaching and Learning (CTL) in environmental science education, including instructional strategies and contextual elements, and to evaluate its effects on students’ cognitive, affective, and behavioural outcomes. Following PRISMA guidelines, 22,437 records were retrieved from Scopus, Google Scholar, and ERIC, then screened using predefined criteria, resulting in 15 studies across primary, secondary, and higher education. The SPIDER framework guided the analysis of sample characteristics, research design, and evaluation methods. Findings show that CTL integrating local environmental knowledge, problem-based learning, and culturally responsive pedagogy improves students’ scientific literacy, environmental awareness, and pro-environmental behaviour, as well as engagement and critical thinking skills. However, challenges remain in connecting classroom learning with real ecological contexts and in supporting reflective and adaptive teaching practices. This review highlights CTL’s potential to foster holistic learning by linking science with authentic environmental issues. Future sustainability-oriented science education should prioritize contextual, experiential, and ethical learning, integrate interdisciplinary approaches, and strengthen teachers’ capacity to design adaptive, locally relevant, and sustainability-driven instruction.